Domain analysis for the construction of a conceptual structure : a case study - Arencibia-Jorge, Ricardo (2021)
This work describes the construction of a conceptual structure, as a result of the domain analysis of the current research on Benign Prostatic Hyperplasia (BPH), through different techniques based on the citations and semantic analysis. A sample which covers all published articles about the disease in mainstream journals was chosen. A total of 1,968 articles from 2000 through 2004 were retrieved from Science Citation Index. Author Co-citation Analysis (ACA) techniques and semantic analysis were used and the results were represented by different informatic programs. A macrostructure of the domain of the current research on BPH was identified through bibliometric techniques. The text mining techniques allowed validation of the identified macrostructure and the obtainment of the most frequent words in the text. The semantic analysis of the most cited reviews on BPH during the studied period allowed the definition of the categories to be used in the structure. Finally, a conceptual structure to be used as controlled (structured) language in the information retrieval, inside of a specialized information system on the approach of the disease is shown.